TINJAUAN YURIDIS KEWENANGAN KEJAKSAAN DALAM MENANGANI KASUS PERDATA (STUDI KASUS PUTUSAN NOMOR 121/PDT.G/2019/PN.CKR) - Tifany Cynthia Sarahdesca; Lucky Ferdiles (Fakultas Hukum Universitas Borobudur, 2023)
The Prosecutor's Office is a government institution that exercises state power in the field of prosecution and other authorities based on law. Based on data from the Attorney General's Office, in 2021 the Attorney General's Office will play an active role as legal representative or attorney for the state or government in civil cases. Therefore, this research will analyze Decision Number 121/Pdt.G/2019/PN.Ckr related to the authority of the prosecutor's office in handling civil cases and how to resolve civil cases handled by the West Java High Prosecutor's Office. The research method used in this research is normative juridical. From the results of the discussion it can be concluded that the prosecutor's authority in handling civil cases in civil cases is carried out by the State Attorney General based on Article 30 paragraph (2) of Law Number 16 of 2004 concerning the Prosecutor's Office of the Republic of Indonesia, Regulation of the Attorney General of the Republic of Indonesia Number 040/A/ JA/12/2010 jo. Republic of Indonesia Attorney General Regulation Number 018/A/JA/07/2014 concerning Standard Operating Procedures. The prosecutor's office can act and have authority for and on behalf of the state both outside and inside the court in the civil and state administrative fields based on the existence of a special power of attorney. The settlement of the civil case in civil case Number 121/Pdt.G/2019/PN.Ckr was carried out by the plaintiffs by filing a lawsuit for an unlawful act using the citizen lawsuit mechanism against state officials (citizen lawsuit).